Resiliensi Sosial Komunitas Petani dalam Menghadapi Alih Fungsi Lahan untuk Proyek PLTB: Kajian Literatur Perspektif Antropologi Pembangunan (Pusat Riset dan Inovasi Nasional, 2026)
Land conversion associated with renewable energy expansion generates profound socio-cultural transformations in agrarian communities. This study aims to analyze how wind power development reshapes agrarian identity, social capital configuration, and the meaning of land within rural society from an anthropology of development perspective. This research applies qualitative literature-based analysis supported by recent peer-reviewed scholarship on land use change, rural transformation, social capital, and political ecology. Conceptual synthesis integrates sustainable livelihood framework, identity negotiation theory, and energy landscape analysis to construct an interpretive analytical model. Findings indicate that agricultural land conversion produces deagrarianization, occupational shifts, and reconfiguration of social stratification. Land is redefined from a genealogical and productive space into infrastructure and investment asset. Social capital grounded in kinship networks, customary institutions, and local organizations functions as a resilience mechanism through risk redistribution, collective solidarity, and participatory negotiation. Energy landscapes restructure symbolic and material relations between community and territory, generating both hybrid identities and conflict dynamics. Inclusive governance determines whether renewable energy fosters adaptive transformation or deepens commodification and exclusion. Renewable energy transition in rural areas requires socio-cultural recognition beyond technical implementation. Integrating local identity, participatory governance, and community ownership strengthens just and sustainable transformation pathways.